A composite dowel bridge in the Czech Republic: Development, optimization and implementation of a railway bridge. Issue 3 (August 2016) - Simon, Pavel; Hrdlicka, Libor; Dráb, Aleš; Zvěřina, Vojtěch
Abstract: The floods in the Czech Republic in the last few decades have resulted in a significant number of bridges having to be rebuilt. Unfortunately, the work meant long‐term traffic closures for railway bridges, coupled with significant costs for renovation and for providing alternative transport services. As a result, the minimum clear headroom above the design flood level required for new bridges and for reconstructing existing bridges has been increased. This initiated a search for new approaches to designing individual parts of bridge crossings, aiming to comply with the stricter conditions. The research aims to decrease costs in comparison with the costs of raising the finished grade level of the railway, especially at places where adjacent sections such as railway stations etc. are connected.